Assessment of urban sanitation status and management gaps in a metropolitan city, Bangladesh: Potential challenges to achieve SDG 6 - Ferdous, Sazia; Chowdhury, Farah Noshin; Ali, Md. Liakath; Bodrud-Doza, Md.; Rahman, Md. Mostafizur (Frontiers in Water, 2022)
Concern have been on the rise around the globe for better sanitation management; being one of the basic human rights, owing especially to the present goal of sustainable development, more specifically Sustainable Development Goal (SDG) 6. Proper sanitation management is a challenging issue in Bangladesh. Purpose of this study was to investigate the current state of sanitation and hygiene facilities and management in Chattogram City, Bangladesh. This study was conducted via questionnaire survey, Key Informant Information (KIIs), Stakeholder meetings, and field visits. Survey was conducted on slum dwellers and non-slum dwellers (formal settlements) of the city. A total of 400(=n) randomly selected respondents were interviewed (200 from each group) from 8 wards of the metropolitan city, 6 KIIs and 3 stakeholder meetings were conducted. Field visits were made to observe the conditions along with a pilot survey to validate the questionnaires. Purposive sampling method was employed for this study while, both descriptive and quantitative statistical analysis was conducted. Statistical analysis of the survey results and field observation found inadequate sanitation and hygiene facilities, insufficient community toilets, improper waste disposal and drainage facilities in the city. Sanitation was worse in slum areas than the non-slum neighborhoods.55.4% slum dwellers had no/little awareness about sanitary system. While, 89% families in slum area use shared-toilets, unhygienic toilet caused different diseases to 63.7% respondents. Drainage conditions were almost equally insufficient in both groups. 65% respondents didn’t have any community toilet in their locality. Sanitation management system is not well-equipped and it’s a pressing need to make better plans and implement sufficient management strategy for the total sanitation of the city.